PENGARUH DISIPLIN, MOTIVASI TERHADAP EFEKTIVITAS KERJA PEGAWAI PADA KANTOR CAMAT KECAMATAN PANYABUNGAN BARAT KAB. MANDAILING NATAL - Muhammad Ardiansyah (Media Bina Ilmiah, 2023)
This study aims to determine the impact of discipline and the effectiveness of employee motivation at the West Panyabungan District Office, Kab. Mandailing Christmas. The sample used in this study were all 35 sub-district office employees using the census method. data analysis using multiple linear regression. The results showed that the Discipline variable, the Motivation variable had a significant effect on the Effectiveness variable, while partially discipline had a significant impact on effectiveness and motivation partially had no significant impact on effectiveness. Based on the results of the overall research and the conclusions obtained that so that employees can further enhance relationships and build synergy among fellow employees at the Panyabungan Barat District Office, Kab. Mandailing Christmas. Because associations are a form of communication event, there are many things that we find by association, some exchange information and also share ideas and attitudes, it is suggested that employees increase the quantity of work in the West Panyabungan District Office, Kab. Mandailing Natal, It is recommended that employees be more disciplined in setting all applicable rules and imposing sanctions on violations committed by violators